Muerte celular inducida por parasporinas y péptidos sintéticos de la parasporina-6 de Bacillus thuringiensis en células de cáncer de cuello uterino y su relación con la vía de adenilato ciclasa (2022)
Cervical cancer is one of the main diseases in women worldwide, multiple non and invasive therapies have been used, such as chemotherapy and hysterectomy, wspecific hich derive cells of noncancerous lineage. For this reason, specific alternative therapies have been studied, such as treatment with parasporins (PS) extracted from Bacillus thuringiensis (Bt) and different anticancer peptides (ACPs). In this work, the cy totoxic effect, and morphological changes present in HeLa cells by pure protein extracts of different Bt strains and synthetic peptides derived from PS6 called PS6DONE and PS6DTWO were evaluated. Additionally, cAMP levels in HeLa cells treated with the two peptides were quantified to determine their relationship with the adenylate cyclase (AC) signaling pathway by means of a direct competitive ELISA assay. The results show a high cytotoxic effect presented by protein extracts from parasporal inclusions agai nst the HeLa cell line associated with necrosis. On the other hand, a cytotoxic effect of the PS6DONE peptide and an increase in cAMP levels were observed, which were accompanied by morphological changes that suggested an autophagy process.